Analysis of Electrical Energy Consumption and Lighting Systems in PT X Lampung Office Buildings - Naimah, Khoirun; Rahmatullah, Abri; Yunesti, Putty (Jambura Journal of Electrical and Electronics Engineering, 2024)
Electricity plays a crucial role in the operations of companies and offices, as highlighted in the 2022 data from the Ministry of Energy and Mineral Resources. The commercial sector recorded an energy usage of 49.65 million BOE (Barrel Oil Equivalent) and 68.891 GWh of electricity consumption. Excessive use of electrical equipment leads to wastage, resulting in higher electricity bills. Thus, there is a need for an efficient system in both lighting and other areas, with efforts focused on enhancing energy efficiency through conservation.This Final Project aims to determine and analyze Energy Consumption Intensity (IKE) values, lighting systems, and identify opportunities for electricity consumption savings at the PT. X Lampung Office Building. The research method involves an initial energy audit and brief measurements on the lighting system. Results indicate that, out of 13 rooms on all three floors, only 5 meet the standards. The analysis identifies opportunities for electricity consumption savings, with a no-cost method at 8.1% and a low-cost method at 9.1%. These findings are expected to serve as recommendations for identifying energy-saving opportunities in Indonesian office buildings.